The Market Valuation of Environmental Capital Expenditures by Pulp and Paper Companies - Clarkson, Peter M.; Li, Yue; Richardson, Gordon D. (The Accounting Review, 2004)
The objective of this study is to examine the market valuation of environmental capital expenditure investment related to pollution abatement in the pulp and paper industry. The total environmental capital expenditure of $8.7 billion by our sample firms during 1989–2000 supports the focus on this industry. In order to be capitalized, an asset should be associated with future economic benefits. The existing environmental literature suggests that investors condition their evaluation of the future economic benefits arising from environmental capital expenditure on an assessment of the firms' environmental performance. This literature predicts the emergence of two environmental stereotypes: low-polluting firms that overcomply with existing environmental regulations, and high-polluting firms that just meet minimal environmental requirements. Our valuation evidence indicates that there are incremental economic benefits associated with environmental capital expenditure investment by low-polluting firms but not high-polluting firms. We also find that investors use environmental performance information to assess unbooked environmental liabilities, which we interpret to represent the future abatement spending obligations of high-polluting firms in the pulp and paper industry. We estimate average unbooked liabilities of $560 million for high-polluting firms, or 16.6 percent of market capitalization.